Funding and performance of amateur and youth organizations in Brazil: a longitudinal analysis of a basketball league - Thiago José Leonardi; Diego Monteiro Gutierrez; Ariane Caroline Sarti; Lucas Arromba de Souza; Paula Simarelli Nicolau; Larissa Rafaela Galatti; Roberto Rodrigues Paes (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: The general aim was to analyze the profile of the teams participating in a basketball regional competition over 8 years (2012-2019). Specifically, we aimed to a) analyze the variation in the number of an organization participating, b) identify the variation in the type of funding, c) verify the existence of a relationship between the performance and the longevity of the organization, d) verify the existence of a relationship between the performance and the type of funding. Methods: The research was designed as an exploratory case study. A total of 86 organizations took part in the league during the period, with 767 different teams playing competitions between U-11 and senior. Results: Instability is the main characteristic of the league. The organizations competing are constantly changing the type of funding and unable to stay in the league for long periods. The research also showed that there is a relation between a stable source of funding and performance. Conclusion: Instability is the main problem in Brazilian youth and amateur basketball organizations. This study presents useful information for managers better understand the problems and difficulties of basketball in Brazil.